23 Exploring the Role of Gut Microbiota in Host Feeding Behavior Among Breeds in Swine. (8th October 2021) - He, Yuqing; Tiezzi, Francesco; Howard, Jeremy T; Huang, Yijian; Gray, Kent A; Maltecca, Christian
Abstract: The present study aimed to explore gut microbiota's overall influence on feeding behavior and identify specific microbes associated with the traits in three commercial swine breeds at different growth stages. Feeding behavior measures were obtained from 651 pigs of three breeds (Duroc, Landrace, and Large White) from 67 to 175 days of age. Seven feeding behavior traits cover the information of feed intake, feeder occupation time, feeding rate, and the number of visits to the feeder. Rectal swabs were collected from each pig at 73 ± 3, 123 ± 4, and 158 ± 4 days of age. DNA was extracted and subjected to 16S rRNA gene sequencing. Sequences were analyzed using the QIIME2. The amplicon sequence variant table was constructed using the DADA2. Mixed linear models were used to perform statistical analyses. Differences in feeding behavior traits among breeds and across time periods were found. The proportion of phenotypic variances explained by the microbiome ranged from 0.10 to 0.26, 0.14 to 0.25, and 0.12 to 0.28 in Duroc pigs, from 0.09 to 0.20, 0.10 to 0.23, and 0.12 to 0.23 in Landrace pigs, from 0.10 to 0.17, 0.11 to 0.19, and 0.10 to 0.31 in Large White pigs at three time points, respectively. A total of 21, 10, and 35 amplicon sequence variants were found to be significantly (q-value < 0.05) associated with feeding behavior traits for Duroc, Landrace, and Large White across three time points. This study demonstrated the importance of the gut microbiome composition in influencing the host feeding behavior and identified multiple microbes associated with the feeding behavior of pigs from either Duroc, Landrace, or Large White breeds at three growth stages. Our study provides insight into the interaction between gut microbiota and feeding behavior and highlights the breed effects in swine microbial studies.